A note on the author citation and typification of Cineraria aurantiaca Hoppe (Tephroseris integrifolia subsp. aurantiaca; Asteraceae) - Bartolucci, Fabrizio; Villani, Mariacristina; Galasso, Gabriele (Phytotaxa, 2021)
The genus Tephroseris (Rchb. in Mössler 1829: 1498) Reichenbach (1841: 87) comprises 15 (Cufodontis 1933) to about 50 (Nordenstam 2007) species distributed in Europe, Asia, and North America. Tephroseris integrifolia (Linnaeus 1753: 925) Holub (1973: 173) subsp. aurantiaca “(Hoppe ex Willdenow 1803: 2081) Nordenstam (1978: 44)” is a name currently accepted for a subspecies native to Austria, Czech Republic, Germany, Hungary, Poland, Switzerland, Ukraine, and Balkan Peninsula (Greuter 2006+, CWG 2021, POWO 2021, WFO 2021). In Italy it was recorded by mistake (Bartolucci et al. 2018, 2020).